Seasonal variation of oxidative biomarkers in gills and digestive glands of the clam Anomalocardia flexuosa and the mangrove oyster Crassostrea rhizophorae. (July 2020) - Sardi, Adriana E.; Sandrini-Neto, Leonardo; da Cunha Lana, Paulo; Camus, Lionel
Abstract: We determined values of antioxidant biomarkers catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione S-transferase (GST) and malondialdehyde (MDA) in two bivalve species from a subtropical system in Brazil. Differences in the biomarkers activities measured in digestive glands and gills sampled at two seasons and in sites with different levels of contamination were tested using univariate and multivariate analyses. Seasonality was the main factor accounting for overall variability. Significant SOD and GPx activities and increased levels of lipid peroxides were detected in summer, while CAT activity was higher in winter. However, biomarkers respond to complex environmental settings as indicated by the significant interaction between season and contamination level. We propose A. flexuosa as a candidate for monitoring studies with sampling occurring at a yearly timescale, and using C. rhizophorae is better suited for designs that include both seasons. Highlights: Baseline levels for antioxidant enzymes are provided fortwotropical and subtropical bivalve species. Seasonal and spatial variation in the biomarker response wasdescribed in bivalves'gills and digestive glands. Multivariate approaches, such as redundancy analysis (RDA), are suggested for multi-species and multi-biomarker studies. The multivariate antioxidant response was species-specific and strongly affected by seasonality. A. flexuosa is an appropriate candidate for monitoring studies with sampling occurring at a yearly timescale. C. rhizophorae is better suited for designs that include both seasons.